Pocong Rush: Endless Runner Game Based On Finite State Machine - Matahari Bhakti Nendya; Daru Redono (Universitas Muhammadiyah Sidoarjo, 2022)
Endless runner Game is a Game where the player will move continuously indefinitely to get the highest point in the Game. Endless runner Game is synonymous with challenges in the form of obstacles and collective items. This study focuses on setting challenges in the non-playable character (NPC) behavior so that they can provide more dynamic challenges. Obstacle, player and NPC settings use the Finite state Machine method which is implemented in an html 5 based Game engine Construct. The implementation results are in the form of an html 5 Game which is then tested through 2 testing stages, namely blackox testing and beta testing. The test results using blackbox testing show that all functionality in the Game can run well, including the behavior of NPCs based on the designed FSM. Beta testing shows that the majority of respondents who have played endless runner Games stated that they like horror Games with local content nuances and the impression of humor and that the average Game difficulty level based on NPC responses to players is 63.75%.